Fourteen pathways between urban transportation and health: A conceptual model and literature review. (June 2021) - Glazener, Andrew; Sanchez, Kristen; Ramani, Tara; Zietsman, Josias; Nieuwenhuijsen, Mark J.; Mindell, Jennifer S.; Fox, Mary; Khreis, Haneen
Abstract: Introduction: Transportation is an integral part of our daily lives, giving us access to people, education, jobs, services, and goods. Our transportation choices and patterns are influenced by four interrelated factors: the land use and built environment, infrastructure, available modes, and emerging technologies/disruptors. These factors influence how we can or choose to move ourselves and goods. In turn, these factors impact various exposures, lifestyles and health outcomes. Aim and methods: We developed a conceptual model to clarify the connections between transportation and health. We conducted a literature review focusing on publications from the past seven years. We complemented this with expert knowledge and synthesized information to summarize the health outcomes of transportation, along 14 identified pathways. Results: The pathways linking transportation to health include those that are beneficial, such as when transportation serves as means for social connectivity, independence, physical activity, and access. Some pathways link transportation to detrimental health outcomes from air pollution, road travel injuries, noise, stress, urban heat islands, contamination, climate change, community severance, and restricted green space, blue space, and aesthetics. Other possible effects may come from electromagnetic fields, but this is not definitive. We define each pathway and summarize its health outcomes. We show that transportation-related exposures and associated health outcomes, and their severity, can be influenced by inequity and intrinsic and extrinsic effect modifiers. Conclusions: While some pathways are widely discussed in the literature, others are new or under-researched. Our conceptual model can form the basis for future studies looking to explore the transportation-health nexus. We also propose the model as a tool to holistically assess the impact of transportation decisions on public health. Highlights: Transportation has beneficial and detrimental impacts on public health. Fourteen pathways link transportation to health, adding five more to the previous published conceptual model. The five new pathways were understudied or unrecognized in previous literature. Each pathway has differing levels of evidence on health effects in the literature. Inequity and modifiers contribute to and may occur because of disproportionate exposures, susceptibility, and health effects.